2021
DOI: 10.3389/fendo.2020.607240
|View full text |Cite
|
Sign up to set email alerts
|

Hypogonadism, Type-2 Diabetes Mellitus, and Bone Health: A Narrative Review

Abstract: One of the complications from chronic hyperglycemia and insulin resistance due to type 2 diabetes mellitus (T2DM) on the hypothalamic-pituitary-gonadal axis in men is the high prevalence of hypogonadotropic hypogonadism (HH). Both T2DM and hypogonadism are associated with impaired bone health and increased fracture risk but whether the combination results in even worse bone disease than either one alone is not well-studied. It is possible that having both conditions predisposes men to an even greater risk for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 241 publications
0
18
0
Order By: Relevance
“…Osteoporosis reduces bone mass, increases bone brittleness, and particularly weakens the regeneration ability of damaged bone. Hence, it has high morbidity, mortality, and disability rates 16 , 17 . The restoration of bone tissue in osteoporosis-affected patients remains a significant problem.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoporosis reduces bone mass, increases bone brittleness, and particularly weakens the regeneration ability of damaged bone. Hence, it has high morbidity, mortality, and disability rates 16 , 17 . The restoration of bone tissue in osteoporosis-affected patients remains a significant problem.…”
Section: Discussionmentioning
confidence: 99%
“…Testosterone may account for this gender difference. Testosterone, usually considered as the main sex steroids in male, has gender-dimorphic impact on the development of metabolic disease, such as type 2 diabetes mellitus [11,12], and in turn, men with T2DM are particularly susceptible to sex hormone disturbance or hypogonadism [13,14]. What is more, preclinical studies demonstrated that testosterone can influence hepatic insulin sensitivity and lipid metabolism [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Hypogonadism is a clinical syndrome in men characterized by the presence of testosterone deficiency and decreased circulating testosterone levels 15,16 . It is associated with symptoms of sexual dysfunction, cardiovascular disease, IR, anaemia and osteoporosis 17,18 . Physically, about 44% of total testosterone (TT) is tightly bound to sex hormone‐binding globulin (SHBG) and 54% is connected with albumin with lower affinity.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 It is associated with symptoms of sexual dysfunction, cardiovascular disease, IR, anaemia and osteoporosis. 17,18 Physically, about 44% of total testosterone (TT) is tightly bound to sex hormone-binding globulin (SHBG) and 54% is connected with albumin with lower affinity. Only 2% of TT is unbound testosterone, which is called free testosterone (FT).…”
Section: Introductionmentioning
confidence: 99%